PEMBERDAYAAN PEREMPUAN MELALUI MAJELIS TAKLIM - Fauziah, Syarifah (PSW, 2015)
Majelis Taklim is an educational institution that is growing and growing community of Islamic society itself whose interests for the benefit of mankind. The growth of informal gatherings among people demonstrated needs and desires of community members will be religious education. On the needs and desires of the broader human in an effort to solve the problems towards a happier life. Increasing demands of pilgrims and the role of non-formal education, raises the awareness and initiative of the scholars and the public as well as to repair, improve and develop the quality and capabilities, as well as the existence and the role and function of Islamic study groups really going well. In this regard the strategic role of women to be active in it and also be a means of empowerment for women themselves, especially in assessing and understanding the true religious teachings and can to implementation in family life, community and nation. Since women are educators first and foremost in the family that determines the success of their children as well as themselves and her husband